Ig heavy chain variable region gene complex of lupus mice exhibits normal restriction fragment length polymorphism (The Rockefeller University Press, 1985)
B cell hyperactivity, hypergammaglobulinemia, and autoantibody expression, the hallmarks of systemic lupus erythematosus, might be associated with structural abnormalities within the Ig heavy chain variable region (Igh-V) gene complex. The Igh-V loci from several lupus- prone mouse strains, their ancestors, and other nonautoimmune mice were therefore analyzed by restriction fragment length polymorphisms with DNA probes corresponding to seven VH gene families. These seven families comprise the majority of the known polymorphic murine VH gene repertoire, including some involved in autoantibody generation. Our study showed that the Igh-V loci from lupus and haplotype-matched nonlupus mice resulted in essentially identical restriction fragment patterns, a finding which suggests that the Igh-V gene complex does not carry a primary defect responsible for autoimmune disease.